Implementasi Router Mikrotik dan Modem Mifi Smartfren sebagai Backup Akses Data dengan Menggunakan Sistem Failover - Muh. Asdar Arfan; Zahir Zainuddin; Rahmania Rahmania (Ainet : Jurnal Informatika, 2019)
Along with the advancement of technology in the telecommunications sector, every government or private agency or office already has internet access. However, there are still a few offices that use this failover system that can support community services as is the case at the Makassar Ministry of Religion. This study aims to determine the configuration, performance and efficiency of the failover system. The method used to test the proxy tool and failover system to all users or clients contained in the office of the Ministry of Religion of Makassar, then carried out a trial of the system and then do a comparison of the number of users or clients contained in ISP 1 whether ISP 2 can backup all user or client contained in ISP 1, the results of the comparison failover system runs as expected and all users or clients contained in ISP 1 can be backed up properly by ISP 2 and it can be concluded that performance and efficiency in failover system usage and Smartfren as an ISP 2 is very helpful to maximize service to the community.